2024
DOI: 10.1186/s12933-023-02098-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of long-term triglyceride-glucose index patterns with the incidence of chronic kidney disease among non-diabetic population: evidence from a functional community cohort

Ning Chen,
Lin-Lin Ma,
Yu Zhang
et al.

Abstract: Background The triglyceride-glucose (TyG) index is a reliable surrogate marker of insulin resistance and previous studies have confirmed the association of TyG index with incident chronic kidney disease (CKD). However, the impact of longitudinal patterns of TyG index on CKD risk among non-diabetic population is still unknown. Therefore, this study aimed to investigate the association of longitudinal patterns of TyG index with incident CKD among non-diabetic population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…In addition, a recent study has established a link between TyG levels and the risk of CKD progression among patients with CKD and DM [ 32 ], and similar findings were observed in this study’s subgroup analysis. Another clinical study showed that TyG can also independently predict the occurrence of CKD in non-diabetic people [ 33 ], while our study found that there was no significant correlation between TyG and CKD risk in non-diabetic participants, which might be a result of different study designs and uncontrolled confounding bias. A recent study on the Korean population showed that TyG was more predictable in the prediction of incident albuminuria than HOMA-IR [ 31 ], and we also found similar results.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, a recent study has established a link between TyG levels and the risk of CKD progression among patients with CKD and DM [ 32 ], and similar findings were observed in this study’s subgroup analysis. Another clinical study showed that TyG can also independently predict the occurrence of CKD in non-diabetic people [ 33 ], while our study found that there was no significant correlation between TyG and CKD risk in non-diabetic participants, which might be a result of different study designs and uncontrolled confounding bias. A recent study on the Korean population showed that TyG was more predictable in the prediction of incident albuminuria than HOMA-IR [ 31 ], and we also found similar results.…”
Section: Discussioncontrasting
confidence: 76%